(untitled) (Nexus International Journal of Science and Education, 2024)
The study "School Environment in Relation to Teachers’ Work Performance of Public Elementary School" investigated the correlation between school environment and teacher performance in public elementary schools in Buhangin District, Division of Davao City. Utilizing a non-experimental quantitative research design, the study surveyed 120 teachers using a modified questionnaire. The results revealed that the school environment, particularly in terms of academic, social, physical, and leadership factors, was extensively positive. Teacher performance was also rated highly, particularly in interpersonal relationships, trust, schoolwork, and achievement. The study found a strong positive correlation between the school environment and teacher performance (r-value = 0.759, p-value = 0.000). Leadership and academic factors were the most significant influencers of teacher performance. These findings underscored the importance of fostering a supportive and well-managed school environment to enhance teacher performance and, consequently, student outcomes. The study recommended regular training for teachers on building a positive school environment and strategic interventions to continuously improve teacher performance.